Factors controlling marine fouling in some Alexandria Harbours, Egypt - RAMADAN, SH.E.; KHEIRALLAH, A.M.; ABDEL-SALAM, KH.M. (Mediterranean Marine Science, 2006)
The present work aims to relate the settlement of marine fouling organisms in three different harbours in Alexandria city which present a wide range of ecological/environmental variations. Theses are the Abu Qir, Eastern and El-Dekheila harbours. Monthly samples of marine fouling were collected from the three harbours by using white roughened polystyrene test panels (12.5x12.5 cm), as well as physicochemical, chemical and other biological data. Results were treated with multivariate statistical analysis (PCA). At the Abu Qir harbour, it was found that water temperature and salinity are the most important environmental factors controlling the temporal distribution of total fouling density, whereas water temperature and chlorophyll a are the most significant environmental factors controlling the total biomass. At the Eastern harbour it was demonstrated that ammonia and phosphate are the most significant environmental factors controlling the temporal distribution and total biomass of fouling organisms. Concerning El-Dekheila harbour, the total density and total biomass of fouling organisms were inversely correlated with the total zooplankton.